Gereja Ekspansif: Tantangan dan Peluang Dalam Mendorong Pertumbuhan Jemaat - Jekson Tulus; Duha, Sang Putra Immanuel; Marpaung, Nona Beta; Daeli, Desimal (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2025)
This research aims to analyze the challenges and opportunities faced by churches in encouraging congregational growth. The main formulation in this research is how expansive churches can overcome existing challenges and take advantage of available opportunities in their efforts to encourage sustainable congregational growth. The church as a religious institution plays an important role in forming a spiritual community and meeting the spiritual needs of its people. The expansive church is a concept that emphasizes the importance of developing proactive strategies and approaches to achieve significant congregational growth. This research method uses a descriptive qualitative research approach. Data collection was carried out through literature studies from books, related journals, interviews with church leaders who are experienced in promoting congregation growth, as well as analysis of related literature. The research results were then analyzed descriptively to identify the main challenges faced by churches in encouraging congregational growth, as well as opportunities that could be exploited. Based on the research results, the conclusion that can be drawn is that expansive churches need to adopt an innovative and inclusive approach in encouraging congregational growth.